ANALISIS TINGKAT EFISIENSI BIAYA KAPASITAS DENGAN MENGGUNAKAN TIME DRIVEN ACTIVITY BASED COSTING (Studi Kasus Kantor Pelayanan Pajak Pratama Tenggarong) - ISLAMY, RABITHAH ALAM (EKONOMIA, 2017)
This study was conducted to determine the amount of capacity cost used by the front office and back office of Service Section on KPP Pratama Tenggarong based on calculations using Time Driven Activity Based Costing and to know the efficiency levels of cost capacity at the front office and back office of Service Section on KPP Pratama Tenggarong based on calculations using Time Driven Activity Based Costing.The analytical tools used in this study are based on the stages in the Time Driven Activity Based Costing method ie calculate the amount of cost incurred or supply capacity in the Service Section, calculate the total capacity of the Service Section officer, calculate the unit cost (cost per minute), calculate the estimated time of completion of an activity and the amount of activity in a year, calculate the used capacity, and calculate the efficiency levels of cost capacity.The result of the study shows that the efficiency level of cost capacity at front office of Service Section shows 93,39% and back office of Service Section shows 92,92% that based on efficiency level according to Mahmudi (2010: 111) are in the category quite efficient.The conclusion from result of the study shows that the Time Driven Activity Based Costing model can be applied to government agencies to know the cost of supply capacity and the cost of the used capacity and the level of efficiency. Information obtained from capacity cost calculations can be used as an evaluation and basic decision-making material.